A coated modified sodium vanadium phosphate composite positive electrode material and a preparation method and application thereof

CN121687910BActive Publication Date: 2026-10-20ZHEJIANG TAIXIN TIMES NEW ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511810280.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-03
Publication Date
2026-10-20
Estimated Expiration
2045-12-03

AI Technical Summary

Technical Problem

传统的高温固相法虽工艺简单,但通常需要长时间的高温煅烧,易导致颗粒粗大、形貌不规则以及成分偏析,从而恶化材料的倍率性能和循环寿命

Benefits of technology

[0036]本申请的有益效果包括但不限于:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121687910B_ABST
    Figure CN121687910B_ABST
Patent Text Reader

Abstract

The application discloses a coated modified sodium vanadium phosphate composite positive electrode material and a preparation method and application thereof, and belongs to the technical field of sodium ion battery positive electrode materials. The coated modified sodium vanadium phosphate composite positive electrode material comprises a core material and a modified carbon source layer coated on the surface of the core material, and the coated modified sodium vanadium phosphate composite positive electrode material is a spherical particle; the core material comprises sodium vanadium phosphate and a doped metal source, the metal source comprises alkaline earth metal and transition metal, the alkaline earth metal is at least one selected from Mg, Ca and Sr, and the transition metal is at least one selected from Fe, Mn, Co and Ni. The core of the coated modified sodium vanadium phosphate composite positive electrode material contains alkaline earth metal elements and transition metal elements for synergistic effect, maintains the lattice stability in the composite positive electrode material, and can inhibit the lattice distortion in the cycle process; meanwhile, the carbon source in the modified carbon source layer is modified, the interface compatibility between components is improved, and the cycle stability is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a coated modified sodium vanadium phosphate composite cathode material, its preparation method and application, belonging to the technical field of sodium-ion battery cathode materials. Background Technology

[0002] With the rapid growth of global demand for renewable energy storage and electric vehicles, developing low-cost, highly safe, and long-life rechargeable battery systems has become a core research goal in the energy sector. While lithium-ion batteries dominate the market, the uneven geographical distribution of lithium resources and rising costs are becoming increasingly prominent issues. Therefore, sodium-ion batteries, which are abundant in resources and inexpensive, are widely considered an important candidate for next-generation large-scale energy storage technology.

[0003] Sodium vanadium phosphate (NVP) cathode materials, with their core advantages of high safety and long lifespan, show great promise in large-scale static energy storage and specific low-speed transportation applications. As a material with a NASICON (sodium superionic conductor) structure, NVP has attracted significant attention due to its stable three-dimensional framework, excellent thermal stability, and high operating voltage. Among them, NVP material has a theoretical specific capacity (approximately 118 mAh / g) and a high average operating voltage (approximately 3.4V vs. Na₂V₂(PO₄)₃). + The advantages of / Na demonstrate its enormous application potential.

[0004] However, the practical application of NVP materials still faces many challenges, as their electrochemical performance largely depends on the material's microstructure, crystallinity, and phase purity. Currently, NVP synthesis methods mainly include high-temperature solid-state methods, hydrothermal / solvothermal methods, and sol-gel methods. While traditional high-temperature solid-state methods are simple, they typically require prolonged high-temperature calcination, which can lead to coarse particles, irregular morphology, and component segregation, thus deteriorating the material's rate performance and cycle life. Materials prepared by the sol-gel method have uniform composition, small and controllable particle size, but are costly and time-consuming. Hydrothermal / solvothermal methods yield products with controllable morphology and high crystallinity, but require sophisticated equipment, involve complex processes, and have low yields, making them unsuitable for industrial production.

[0005] Therefore, developing a simple, low-cost, and high-performance coated modified sodium vanadium phosphate composite cathode material and its preparation method is of great significance for promoting its industrial application and advancing the development of high-performance sodium-ion batteries. Summary of the Invention

[0006] To address the aforementioned issues, a modified sodium vanadium phosphate composite cathode material is provided. This core material contains alkaline earth metal ions and transition metal elements, which work synergistically to maintain lattice stability in the composite cathode material and suppress lattice distortion during cycling. Simultaneously, the carbon source in the modified carbon source layer is modified to improve the interfacial compatibility between the components, further enhancing cycling stability.

[0007] One aspect of this application provides a coated modified sodium vanadium phosphate composite cathode material, the coated modified sodium vanadium phosphate composite cathode material comprising a core material and a modified carbon source layer coated on the surface of the core material, the coated modified sodium vanadium phosphate composite cathode material being spherical particles; The core material includes sodium vanadium phosphate and a metal element doped therein. The metal element includes an alkaline earth metal element and a transition metal element. The alkaline earth metal element is selected from at least one of Mg, Ca, and Sr, and the transition metal element is selected from at least one of Fe, Mn, Co, and Ni.

[0008] In this application, by adding alkaline earth metals and transition metals to the core in a synergistic effect, alkaline earth metals readily enter the crystal lattice to form a solid solution, and Na is generated through charge compensation. + Vacancies widen ion transport channels and reduce Na+ + The migration barrier increases the ion diffusion rate and can also maintain lattice stability and suppress lattice distortion during cycling; transition metal ions have variable valence states, which lower the electron transport barrier, improve the material conductivity, increase the battery discharge capacity, and extend cycle life.

[0009] Optionally, the modified carbon source includes N-ethylcarbazole, polypyrrole, and concentrated sulfuric acid.

[0010] Optionally, the modified carbon source is prepared as follows: (1) Dissolve N-ethylcarbazole in concentrated sulfuric acid, mix well, react at 40-50℃ for 7-9h, wash with water until neutral, and dry to obtain sulfonated N-ethylcarbazole; (2) After the sulfonated N-ethylcarbazole is mixed evenly with polypyrrole, it is dried to obtain the modified carbon source.

[0011] By dissolving N-ethylcarbazole in concentrated sulfuric acid to form sulfonic acid groups on the surface of N-ethylcarbazole, and then mixing it with polypyrrole, the structure of the modified carbon source layer can be made dense and stable. This not only improves the conductivity of the composite cathode material, but also avoids direct contact between sodium vanadium phosphate and the metal source and the electrolyte, suppresses the side reactions between the active components in the core material and the electrolyte, thereby reducing the interfacial resistance between the core material and the electrolyte and improving the cycle performance of the cathode material.

[0012] Optionally, the mass ratio of N-ethylcarbazole to concentrated sulfuric acid is 1:(8-10).

[0013] At this ratio, sulfonic acid groups can be introduced onto N-ethylcarbazole, improving its interfacial compatibility with polypyrrole and forming a dense modified carbon source layer. This better isolates the core active material from direct contact with the electrolyte, reduces the probability of side reactions, and improves the cycle life of the composite cathode material. In addition, N-ethylcarbazole contains a conjugated structure, which can enhance its cycle life under higher temperature conditions.

[0014] Optionally, the mass ratio of the sulfonated N-ethylcarbazole to polypyrrole is 1:(0.3-0.6).

[0015] At this ratio, both N-ethylcarbazole and polypyrrole have conjugated systems, which can improve the conductivity of the modified carbon source layer, reduce the Na ion migration barrier, and improve rate performance. In addition, the surface of polypyrrole is rich in functional groups such as amino and pyrrole rings, which can form coordination with metal ions, improve interfacial bonding, and prevent the coating layer from falling off. The two work together to improve the cycle life of the composite cathode material.

[0016] Another aspect of this application provides a method for preparing a coated and modified sodium vanadium phosphate composite cathode material, the method comprising the following steps: S1. A mixed slurry is obtained by uniformly mixing phosphorus source, sodium source, vanadium source, alkaline earth metal source, transition metal source, binder and solvent. S2. The mixed slurry in step S1 is spray-dried to obtain spherical particle precursors; S3. Disperse the modified carbon source in an organic solvent to obtain a modified carbon source mixture. Add the spherical particle precursor from step S2 to the modified carbon source mixture and mix evenly so that the modified carbon source is evenly coated on the surface of the spherical particle precursor. Perform secondary spray drying to obtain an intermediate. S4. The intermediate from step S3 is sintered in a moving bed reactor to finally obtain the coated modified sodium vanadium phosphate composite cathode material.

[0017] Optionally, the alkaline earth metal source and the transition metal source are at least one of the nitrates or oxides corresponding to each metal element.

[0018] Optionally, the phosphorus source includes at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium hydrogen phosphate, metaphosphoric acid, butyl phosphate, and phosphoric acid.

[0019] Optionally, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate and disodium hydrogen phosphate, sodium fluoride, sodium chloride, and sodium sulfate.

[0020] Optionally, the vanadium source includes at least one of ammonium metavanadate, vanadium trioxide, vanadium difluoride, and vanadium hydroxide.

[0021] Optionally, the molar ratio of the sodium source, phosphorus source and vanadium source is 3:3:2.

[0022] Optionally, the molar ratio of the alkaline earth metal source to the transition metal source is 1:(1.2-1.8).

[0023] At this ratio, the synergistic effect can be maximized. Transition metals can build an electronic conduction network, significantly improving conductivity, while alkaline earth metals can effectively suppress transition metal agglomeration and lattice distortion, balancing high rate performance and long cycle life.

[0024] Optionally, the inlet air temperature of the spray drying in step S2 is 180-300℃, and the outlet air temperature is 80-100℃.

[0025] Optionally, the spray drying temperature in step S3 is 180-300℃, and the outlet air temperature is 80-100℃.

[0026] Spray drying at the specified temperature not only results in a rapid dehydration rate but also preserves the crystal structure of the mixed slurry, maintaining its stability. If the temperature is below 180℃, the drying rate is insufficient, and droplets are prone to adhesion, leading to severe agglomeration of components in the mixed slurry. If the temperature is above 300℃, the surface of the mixed slurry is excessively sintered, forming dense, hard agglomerates. Subsequent pulverization processes will destroy the spherical structure, reducing the electrochemical performance of the composite cathode material.

[0027] Optionally, the median particle size of the spherical particle precursor described in step S2 is 2.5-40 μm.

[0028] Preferably, the median particle size of the spherical particle precursor in step S2 is 8-15 μm.

[0029] At this particle size, the uniformity of the modified carbon source coating on the spherical particle precursor can be improved, the density of the modified carbon source layer can be increased, the coating stability of the modified carbon source layer and the spherical particle precursor can be further improved, thereby improving the electronic conductivity and cycle stability.

[0030] Optionally, the material movement speed in the moving bed reactor described in step S4 is 0.2-1.0 m / h.

[0031] At this material movement speed, the modified carbon source has sufficient time to achieve carbon source pyrolysis and uniform deposition, thereby improving the performance stability and uniformity of the product.

[0032] Optionally, the sintering temperature in step S4 is 600-850℃, and the gas flow rate is 0.03cm / s-7.8cm / s.

[0033] Preferably, the sintering temperature in step S4 is 700-780℃, and the gas flow rate is 1.0cm / s-3.0cm / s.

[0034] Optionally, the gas in the moving bed reactor is selected from at least one of alkanes, carbon monoxide, hydrogen, nitrogen, and helium.

[0035] Another aspect of this application provides the application of the coated modified sodium vanadium phosphate composite cathode material described above or the coated modified sodium vanadium phosphate composite cathode material prepared by the preparation method described above in liquid sodium-ion batteries, semi-solid sodium-ion batteries or all-solid sodium-ion batteries.

[0036] The beneficial effects of this application include, but are not limited to: 1. According to the coated modified sodium vanadium phosphate composite cathode material of this application, N-ethylcarbazole is dissolved in concentrated sulfuric acid to form sulfonic acid groups on the surface of N-ethylcarbazole, and then mixed with polypyrrole. This can make the structure of the modified carbon source layer dense and stable, which not only improves the conductivity of the composite cathode material, but also avoids direct contact between sodium vanadium phosphate and the metal source and the electrolyte, suppresses the side reactions between the active components in the core material and the electrolyte, thereby reducing the interfacial resistance between the core material and the electrolyte and improving cycle stability.

[0037] 2. According to the coated modified sodium vanadium phosphate composite cathode material of this application, the addition of alkaline earth metals and transition metals to the core material has a synergistic effect, which can not only broaden the ion transport channels but also reduce Na+. + The migration barrier enhances the ion diffusion rate, maintains lattice stability, suppresses lattice distortion during cycling, and extends cycle life.

[0038] 3. According to the coated modified sodium vanadium phosphate composite cathode material of this application, polypyrrole and N-ethylcarbazole synergistically improve the cycle life of the composite cathode material. The surface of polypyrrole is rich in functional groups such as amino and pyrrole rings, which can form coordination with metal ions, enhance the interfacial bonding force, prevent the coating layer from falling off, and isolate the side reaction between the electrolyte and the core active material. Attached Figure Description

[0039] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram of the XRD pattern involved in Embodiment 1 of this application.

[0040] Figure 2 This is a schematic diagram of the charge-discharge curves involved in Embodiment 2 and Comparative Example 2 of this application. Detailed Implementation

[0041] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0042] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0043] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0044] The concentrated sulfuric acid mentioned in this application is a 98% concentrated sulfuric acid solution; CAS number for N-ethylcarbazole: 86-28-2; CAS number for polypyrrole: 30604-81-0.

[0045] Example 1 This embodiment relates to a coated and modified sodium vanadium phosphate composite cathode material, the preparation method of which includes the following steps: S1. Weigh sodium dihydrogen phosphate (sodium source and phosphorus source) and vanadium trioxide (vanadium source) according to the molar ratio of sodium source, phosphorus source and vanadium source of 3:3:2. Then weigh magnesium oxide and ferric oxide according to the molar ratio of magnesium element, iron element and sodium source of 1000:0.1:0.12. Add sodium carboxymethyl cellulose sodium with a total mass content of 2% of the core material. Then add deionized water with a total mass of 5 times the core material. Mix evenly by ultrasonication to obtain a mixed slurry. S2. The mixed slurry in step S1 is spray-dried to obtain spherical particle precursor. The inlet air temperature of the spray dryer is 180℃, the outlet air temperature is 80℃, and the median particle size of the spherical particle precursor is 2.5μm. S3. Disperse the modified carbon source in 5 times the amount of anhydrous ethanol to obtain a modified carbon source mixture. Add the spherical particle precursor from step S2 to the modified carbon source mixture and mix evenly. The mass ratio of modified carbon source to spherical particle precursor is 0.03:1, so that the modified carbon source is evenly coated on the surface of the spherical particle precursor. Perform secondary spray drying. The inlet air temperature of the spray drying is 300℃ and the outlet air temperature is 120℃ to obtain an intermediate. The modified carbon source is prepared as follows: (1) N-ethylcarbazole was dissolved in concentrated sulfuric acid at a mass ratio of 1:8. After stirring and mixing evenly, the mixture was reacted at 40°C for 9 hours. After washing with water until neutral, the mixture was dried to obtain sulfonated N-ethylcarbazole. (2) After the sulfonated N-ethylcarbazole and polypyrrole are mixed evenly, the mass ratio of sulfonated N-ethylcarbazole to polypyrrole is 1:0.3, and the mixture is dried to obtain the modified carbon source; S4. The intermediate from step S3 is sintered in a moving bed reactor. The material moving speed of the intermediate from top to bottom in the moving bed reactor is 0.2 m / h. Carbon monoxide gas is introduced into the moving bed reactor at a flow rate of 0.03 cm / s. The sintering temperature in the moving bed reactor is 600℃. Finally, the coated modified sodium vanadium phosphate composite cathode material is obtained.

[0046] Example 2 This embodiment relates to a coated and modified sodium vanadium phosphate composite cathode material, the preparation method of which includes the following steps: S1. Weigh sodium carbonate (sodium source), ammonium dihydrogen phosphate (phosphorus source), and vanadium difluoride (vanadium source) according to the molar ratio of sodium source, phosphorus source, and vanadium source of 3:3:2. Then weigh calcium oxide and nickel nitrate according to the molar ratio of calcium element, nickel element, and sodium source of 1000:0.1:0.18. Add 2% of carboxymethyl cellulose of the total mass content of the core material. Then add 6 times the total mass of deionized water of the core material. After ultrasonic mixing, a mixed slurry is obtained. S2. The mixed slurry in step S1 is spray-dried to obtain spherical particle precursor. The inlet air temperature of the spray dryer is 300℃, the outlet air temperature is 120℃, and the median particle size of the spherical particle precursor is 40μm. S3. Disperse the modified carbon source in 8 times the amount of anhydrous ethanol to obtain a modified carbon source mixture. Add the spherical particle precursor from step S2 to the modified carbon source mixture and mix evenly. The mass ratio of modified carbon source to spherical particle precursor is 0.03:1, so that the modified carbon source is evenly coated on the surface of the spherical particle precursor. Perform secondary spray drying. The inlet air temperature of the spray drying is 180℃ and the outlet air temperature is 80℃ to obtain an intermediate. The modified carbon source is prepared as follows: (1) N-ethylcarbazole was dissolved in concentrated sulfuric acid at a mass ratio of 1:10. After stirring and mixing evenly, the mixture was reacted at 50°C for 7 hours. After washing with water until neutral, the mixture was dried to obtain sulfonated N-ethylcarbazole. (2) After the sulfonated N-ethylcarbazole and polypyrrole are mixed evenly, the mass ratio of sulfonated N-ethylcarbazole to polypyrrole is 1:0.6, and the mixture is dried to obtain the modified carbon source; S4. The intermediate from step S3 is sintered in a moving bed reactor. The material moving speed of the intermediate in the moving bed reactor from top to bottom is 1.0 m / h. Carbon monoxide gas is introduced into the moving bed reactor at a flow rate of 7.8 cm / s. The sintering temperature in the moving bed reactor is 850℃. Finally, the coated modified sodium vanadium phosphate composite cathode material is obtained.

[0047] Example 3 This embodiment relates to a coated and modified sodium vanadium phosphate composite cathode material, the preparation method of which includes the following steps: S1. Weigh sodium chloride (sodium source), metaphosphoric acid (phosphorus source), and vanadium hydroxide (vanadium source) according to the molar ratio of sodium source, phosphorus source, and vanadium source of 3:3:2. Then weigh strontium oxide and manganese dioxide according to the molar ratio of strontium to manganese to sodium source of 1000:0.1:0.15. Add 2% of carboxymethyl cellulose of the total mass content of the core material. Then add 5 times the total mass of deionized water of the core material. Mix evenly by ultrasonication to obtain a mixed slurry. S2. The mixed slurry in step S1 is spray-dried to obtain spherical particle precursor. The inlet air temperature of the spray dryer is 240℃, the outlet air temperature is 100℃, and the median particle size of the spherical particle precursor is 10μm. S3. Disperse the modified carbon source in 8 times the amount of anhydrous ethanol to obtain a modified carbon source mixture. Add the spherical particle precursor from step S2 to the modified carbon source mixture and mix evenly. The mass ratio of modified carbon source to spherical particle precursor is 0.03:1, so that the modified carbon source is evenly coated on the surface of the spherical particle precursor. Perform secondary spray drying. The inlet air temperature of the spray drying is 260℃ and the outlet air temperature is 110℃ to obtain an intermediate. The modified carbon source is prepared as follows: (1) N-ethylcarbazole was dissolved in concentrated sulfuric acid at a mass ratio of 1:9. After stirring and mixing evenly, the mixture was reacted at 45°C for 6.5 h. After washing with water until neutral, it was dried to obtain sulfonated N-ethylcarbazole. (2) After the sulfonated N-ethylcarbazole and polypyrrole are mixed evenly, the mass ratio of sulfonated N-ethylcarbazole to polypyrrole is 1:0.5, and the mixture is dried to obtain the modified carbon source; S4. The intermediate from step S3 is sintered in a moving bed reactor. The material moving speed of the intermediate from top to bottom in the moving bed reactor is 0.6 m / h. Carbon monoxide gas is introduced into the moving bed reactor at a flow rate of 3.5 cm / s. The sintering temperature in the moving bed reactor is 750℃. Finally, the coated modified sodium vanadium phosphate composite cathode material is obtained.

[0048] Example 4 The difference between this embodiment and Embodiment 3 is that polypyrrole is not added to the modified carbon source, while the rest is the same as in Embodiment 3.

[0049] Example 5 The difference between this embodiment and embodiment 3 is that the mass ratio of sulfonated N-ethylcarbazole to polypyrrole in step (2) is 1:0.1, and the rest is the same as in embodiment 3.

[0050] Example 6 The difference between this embodiment and embodiment 3 is that the total mass content of strontium and manganese in the core material in step S1 is 0.1‰ and 0.01‰, respectively, while the rest is the same as in embodiment 3.

[0051] Example 7 The difference between this embodiment and embodiment 3 is that the material moving speed in the moving bed reactor in step S4 is 12 m / h, while the rest is the same as in embodiment 3.

[0052] Example 8 The difference between this embodiment and embodiment 3 is that the gas flow rate in step S4 is 10 cm / s, while the rest is the same as in embodiment 3.

[0053] Example 9 The difference between this embodiment and embodiment 3 is that the sintering temperature in step S4 is 500℃, while the rest is the same as in embodiment 3.

[0054] Comparative Example 1 The difference between this comparative example and Example 3 is that the modified carbon source is directly mixed with phosphorus source, sodium source, vanadium source, strontium element, manganese element, polytetrafluoroethylene and anhydrous ethanol, and the modified sodium vanadium phosphate composite electrode material is obtained by spray drying. Steps S3 and S4 are not performed. The rest is the same as in Example 3.

[0055] Comparative Example 2 The difference between this comparative example and Example 3 is that strontium and manganese are not added; otherwise, they are the same as in Example 3.

[0056] Comparative Example 3 The difference between this comparative example and Example 3 is that the modified carbon source is replaced with glucose, while the rest is the same as Example 3.

[0057] Comparative Example 4 Sodium vanadium phosphate cathode material was prepared using the preparation method described in Example 1 of Chinese Patent CN116864660B.

[0058] Test Example 1 The coated modified sodium vanadium phosphate cathode materials or sodium vanadium phosphate cathode materials prepared in Examples 1-9 and Comparative Examples 1-4 were mixed with conductive carbon black and PVDF at a mass ratio of 8:1:1, respectively. N-methylpyrrolidone was added to form a slurry, which was uniformly coated on aluminum foil. After vacuum drying at 120°C for 12 hours, the mixture was stamped into a disc with a diameter of 12 mm as the cathode, with a sodium metal disc as the anode. The electrolyte was 1 mol / L sodium hexafluorophosphate, and the solvent composition was EC, DMC, and EMC in a volume ratio of 1:1:1. Glass fiber was used as the separator. Button cells were assembled in a glove box under a high-purity argon atmosphere. The discharge specific capacity, 100-cycle capacity retention rate, and high-temperature performance of the above cells were tested. The specific test methods are as follows: 1. Discharge specific capacity test: On the LANDCT2001A battery test cabinet, the above button battery was first charged to 3.8V with a constant current of 0.1C, and then discharged to 2.5V. The specific capacity was calculated by measuring the discharge capacity. The calculation formula is: Discharge specific capacity = Discharge capacity / Mass of active material.

[0059] 2. 100-cycle capacity retention test: On the LAND CT2001A battery test cabinet, under constant temperature of 25℃, button batteries were charged and discharged at 0.5C current between 2.5V and 3.8V. The test was stopped after 100 cycles or when the capacity decreased to below 70% of the initial capacity. The 100-cycle capacity retention rate = (100th cycle discharge capacity / initial 0.5C discharge capacity) * 100%. 3. High-temperature performance test: The assembled button cells were subjected to a 50-cycle capacity test at 55℃, and the test results are shown in Table 1.

[0060] Table 1

[0061] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A coated and modified sodium vanadium phosphate composite cathode material, characterized in that, The coated modified sodium vanadium phosphate composite cathode material includes a core material and a modified carbon source layer coated on the surface of the core material. The coated modified sodium vanadium phosphate composite cathode material is a spherical particle. The core material includes sodium vanadium phosphate and a doped metal source, wherein the metal source includes an alkaline earth metal and a transition metal, wherein the alkaline earth metal is selected from at least one of Mg, Ca, and Sr, and the transition metal is selected from at least one of Fe, Mn, Co, and Ni. The modified carbon source is prepared as follows: (1) Dissolve N-ethylcarbazole in concentrated sulfuric acid, mix well, react at 40-50℃ for 7-9h, wash with water until neutral, and dry to obtain sulfonated N-ethylcarbazole; (2) After the sulfonated N-ethylcarbazole and polypyrrole are mixed evenly, the mixture is dried to obtain the modified carbon source; The preparation method includes the following steps: S1. After uniformly mixing phosphorus source, sodium source, vanadium source, binder and solvent, a mixed slurry is obtained; S2. The mixed slurry in step S1 is spray-dried to obtain spherical particle precursors; S3. Disperse the modified carbon source in an organic solvent to obtain a modified carbon source mixture. Add the spherical particle precursor from step S2 to the modified carbon source mixture and mix evenly so that the modified carbon source is evenly coated on the surface of the spherical particle precursor. Perform secondary spray drying to obtain an intermediate. S4. The intermediate in step S3 is sintered in a moving bed reactor to finally obtain the coated modified sodium vanadium phosphate composite cathode material. The sintering temperature in step S4 is 600-850℃; The gas in the moving bed reactor is selected from at least one of alkanes, carbon monoxide, hydrogen, nitrogen, and helium.

2. The coated and modified sodium vanadium phosphate composite cathode material according to claim 1, characterized in that, The mass ratio of N-ethylcarbazole to concentrated sulfuric acid is 1:(8-10); and / or The mass ratio of the sulfonated N-ethylcarbazole to polypyrrole is 1:(0.3-0.6).

3. The coated and modified sodium vanadium phosphate composite cathode material according to claim 1, characterized in that, The molar ratio of the alkaline earth metal to the transition metal is 1:(1.2-1.8).

4. The coated and modified sodium vanadium phosphate composite cathode material according to claim 1, characterized in that, The inlet air temperature of the spray dryer described in step S2 is 180-300℃, and the outlet air temperature is 80-100℃; and / or The inlet air temperature of the spray drying process described in step S3 is 180-300℃, and the outlet air temperature is 80-100℃.

5. The coated and modified sodium vanadium phosphate composite cathode material according to claim 1, characterized in that, The median particle size of the spherical particle precursor described in step S2 is 2.5-40 μm.

6. The coated and modified sodium vanadium phosphate composite cathode material according to claim 1, characterized in that, In step S4, the material movement velocity in the moving bed reactor is 0.2-1.0 m / h; and / or The gas flow rate is 0.03 cm / s to 7.8 cm / s.

7. The application of the coated modified sodium vanadium phosphate composite cathode material according to any one of claims 1-6 in liquid sodium-ion batteries, semi-solid sodium-ion batteries or all-solid sodium-ion batteries.

Citation Information

Patent Citations

  • A sodium vanadium phosphate cathode material and its application in vehicle batteries.

    CN116864660B

  • Carbon-coated cation-doped sodium vanadium phosphate positive electrode material as well as preparation method and application thereof

    CN116706036A